Supporting Immigrants in Workplace Language Learning: Challenges for Organizations - Jug Došler, Anita (Two Homelands, 2023)
This article deals with how to support adult immigrants in developing work-related language skills from a work organization perspective. Developing such skills is important not only for the successful performance of work tasks but also for successful social integration into the work and social environment. The article is based on a study using combined quantitative and qualitative methodology. The authors were interested in how language teaching in the workplace can be organized for foreigners and what challenges are faced by Slovenian organizations employing foreigners. The research conclusions are developed with practice recommendations for such organizations.